TANGGUNG JAWAB PEMILIK KAPAL DALAM PERJANJIAN CARTER KAPAL BERDASARKAN WAKTU DI PT BUANA JAYA PRATAMA (STUDI KASUS PUTUSAN PENGADILAN TINGGI NOMOR: 745/PDT/2016/PT.DKI.) - Kenny Jusup; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
Any activity undertaken by a person in order to fulfill his or her life needs will surely relate and use the treaty law. However, both in the manufacture and implementation of the agreement, did not rule out other human possibilities. therefore, a legal norm is required so that in the process of interpersonal life there is peace and order. The interesting problem to be raised in this thesis is about the misconduct done by PT Haluan Segara Line to PT Buana Jaya pratama. In such cases, there is a contractual relationship between PT Buana Jaya Pratama and PT Haluan Segara Line during the charter lease charter agreement there is a rule to comply with all rules contained in the agreement. So that where the time of the agreement has expired, PT Haluan Segara Line does not want to pay the vessel on the ground that PT Haluan Segara Line does not make an agreement on the lease of the vessel, there was an act of default.